Preliminary results of the first paleoseismologic study along the Bucaramanga fault, Colombia (2009)
The Bucaramanga Fault is the fault in Colombia with the strongest physiographic expression. It extends from Aguachica in the north southward to Bucaramanga and beyond. Abundant morphotectonic indices testify to a high degree of activity during the Quaternary. A recent detailed regional study along the main fault corridor has identified several promising locations with potential for paleoseismologic trench studies. The site actually selected was situated in a limestone quarry at 4,5 km north of Bucaramanga town on the north bank of the Surata river. It concerns a small tectonic basin in a hanging valley situated 250 m to the west of the main Bucaramanga Fault and is filled with a series of colluvial wedges and fine grained lacustrine deposits with abundant organic material. Detailed logging of the outcrop face at a scale of 1:10 was carried out and seventeen samples were taken from the organic rich levels for radiocarbon dating. Basin evolution is controlled by movement of the principal fault trace in which each sedimentary level is a registration of co-seismic subsidence and represents the stratigraphic evidence of pre-historic earthquakes. The result of radiocarbon dating show ages that range from 8300-930 y/BP and a preliminary interpretation suggests the occurrence of 8 holocene seismic events during the last 8300 years and magnitudes in the order of 6,5-7,0 Ms.